2018
DOI: 10.1002/aoc.4714
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylative Suzuki coupling and alkoxycarbonylation of aryl halides using palladium supported on phosphorus‐doped porous organic polymer as an active and robust catalyst

Abstract: Developing highly active catalysts with the combined advantages of molecular and solid catalysis is considered as the “Holy Grail” in the area of catalysis research. Herein, a phosphorus‐doped porous polymer‐immobilized palladium was successfully developed as an efficient, robust, and recyclable catalyst for the carbonylative Suzuki coupling and alkoxycarbonylation reactions of aryl halides. Rather than just as an immobilizing molecular catalyst, palladium supported on phosphorus‐doped porous organic polymer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 53 publications
(121 reference statements)
0
12
0
Order By: Relevance
“…Solid-state 31 P NMR spectra of PQPBr and PQPBr-2OH in Figure 4b showed a main peak with a small peak at around 19.8 ppm and −7.7 ppm, respectively. The peak at 19.8 ppm can be attributed to the phosphorus atoms of the phosphonium salts [45,51], while the small peak at around −7.7 ppm should be assigned to a small amount of unfunctionalized phosphine [44,51]. These findings further indicated that most of P atoms in PQPBr and PQPBr-2OH was successfully alkylated by alkyl bromide.…”
Section: Characterizations Of the Polymeric Catalystsmentioning
confidence: 79%
See 1 more Smart Citation
“…Solid-state 31 P NMR spectra of PQPBr and PQPBr-2OH in Figure 4b showed a main peak with a small peak at around 19.8 ppm and −7.7 ppm, respectively. The peak at 19.8 ppm can be attributed to the phosphorus atoms of the phosphonium salts [45,51], while the small peak at around −7.7 ppm should be assigned to a small amount of unfunctionalized phosphine [44,51]. These findings further indicated that most of P atoms in PQPBr and PQPBr-2OH was successfully alkylated by alkyl bromide.…”
Section: Characterizations Of the Polymeric Catalystsmentioning
confidence: 79%
“…CO 2 (99.99%) was supplied by a local manufacturer (Liupanshui, China). Tris(4-vinylphenyl)phosphane and poly(tris(4-vinylphenyl)phosphine) (POL-PPh 3 ) were prepared as previously reported [45].…”
Section: Methodsmentioning
confidence: 99%
“…Sulfuric acid (98%) was obtained from Tianjin Guangfu Chemical Reagent (Tianjin, China). Tris(4-vinylphenyl)phosphine (TVP) was prepared as our previous report [39]. 4-Vinylbenzyl-tris-(4-vinylphenyl)-phosphonium chloride (QP) was prepared by a simple reaction of TVP and 4-vinylbenzyl chloride [40].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a related carbonylative coupling of aryl halides with arylboronic acids using carbon monoxide as the C1 source was reported by Lei and co-workers. 54 They showed that in the presence of only 0.25 mol% of palladium nanoparticles supported on phosphorus-doped porous organic polymer (Pd@POP-Ph 3 P) as the catalyst and 2 equiv. of K 2 CO 3 as a base, reaction of a variety of functionalized aryl iodides 35 with a wide range of arylboronic acids 36 under a CO atmosphere furnished the respective biaryl ketones 37 in high to almost quantitative yields ( Scheme 11b ).…”
Section: Palladium Nanoparticles-based Catalystsmentioning
confidence: 99%